Systematic lidar observations of Saharan dust layers over Athens, Greece in the frame of EARLINET project (2004–2006) - A. Papayannis; R. E. Mamouri; V. Amiridis; S. Kazadzis; S. Kazadzis; C. Pérez; G. Tsaknakis; P. Kokkalis; J. M. Baldasano; J. M. Baldasano (Annales Geophysicae, 2009)
In this paper we present a statistical analysis on the geometrical and optical properties of Saharan dust layers observed over Athens, Greece, in a three-year period from 1 January 2004 up to 31 December 2006. The observations of the vertical aerosol profile were performed by the multi-wavelength (355-532-1064-387-607 nm) Raman lidar system of the National Technical University of Athens (NTUA) operated in the city of Athens (37°98' N, 23°77' E), Greece, in the frame of the European Aerosol Research Lidar Network (EARLINET-ASOS) project. The number of dust events was greatest in late spring, summer, and early autumn periods. This was evident also by aerosol observations during dust outbreaks obtained from the Moderate Resolution Imaging Spectroradiometer (MODIS). In our lidar measurements, multiple aerosol dust layers of variable thickness (680–4800 m) were observed. The center of mass of these layers was located in altitudes between 1600 and 5800 m. However, the mean thickness of the dust layer typically stayed around 2700 m and the corresponding mean center of mass was of the order of 2900 m. The top of the dust layer ranged from 2000 to 8000 m, with a mean value of the order of 4700 m. MODIS observations during dust outbreaks showed that the AOD values at 550 nm ranged between 0.3–0.6, while the corresponding Angström exponent (AE) values were of the order of 0.5–0.65, indicating the presence of rather large particles.